1987
DOI: 10.1111/j.1468-2257.1987.tb00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Return Migration to Eastern Kentucky and the Stem Family Concept

Abstract: This research provides a conceptual framework-based on the stem family concept-with which to explore the cyclical nature of return migration to Eastern Kentucky. A generalized six-phase migration model is developed within a stem familyldiffusion context to explain how the socioeconomic characteristics of return migrants have varied in response to economic changes outside Appalachia. The role of awareness space on channeling migration flows is also examined.Responses from 119 households in Laurel, Pike, and Pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…They are infrequently used as sources of information about migration, but have the potential to illuminate nuances in place attachment and migration decisions across generations and socio-economic groups. The Appalachian counties of eastern Kentucky, where family reunions are common, are notable for their previously high rates of return migration facilitated by strong kinship networks and place attachment (see Bohland 1970;White 1987;Obermiller and Rappold 1990). A large literature already documents the migration characteristics of this region's population (see, e.g., Rowles and Watkins 1995;Obermiller andHowe 2001, 2004;Obermiller 2004;Watkins et al 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are infrequently used as sources of information about migration, but have the potential to illuminate nuances in place attachment and migration decisions across generations and socio-economic groups. The Appalachian counties of eastern Kentucky, where family reunions are common, are notable for their previously high rates of return migration facilitated by strong kinship networks and place attachment (see Bohland 1970;White 1987;Obermiller and Rappold 1990). A large literature already documents the migration characteristics of this region's population (see, e.g., Rowles and Watkins 1995;Obermiller andHowe 2001, 2004;Obermiller 2004;Watkins et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…But many people do choose to stay in rural Appalachia, much as they do in other rural communities throughout the country. Numerous studies have investigated the movement of migrants into and out of the region (see, e.g., Pickard 1981;Rowles and Watkins 1995;Berry 2000;Obermiller and Howe 2000, 2004Obermiller 2004, Watkins et al 2004Alexander 2005;Pollard 2005), and others focus on the importance of social networks and place attachment in facilitating return migration (e.g., White 1987White , 1989White and Brunn 1994). Yet other scholars have identified ways in which out-migrants from the region have transported their home to distant cities through social organizations and settlement patterns within cities external to the region (see, e.g., Borman and Obermiller 1994;Guy 2000;Johnson 2000).…”
Section: Place Attachment Immobility and Rural Communities Of Appalmentioning
confidence: 99%
“…"Going home" can also play an important part in rural growth. In Kentucky, White (1987) found that most migrants were return migrants and their motivations were more sociocultural than job-related. There are few theoretical studies of repeat migration and there is a need to differentiate between types of migrants in the modeling process (Dierx, 1988), as well as to consider the duration of previous migration (Krumm and Kelly, 1988).…”
Section: Migration Into Nonmetropolitan Areasmentioning
confidence: 98%
“…In such communities, return migrants represent a sizeable share of in-migrants. White (1987), for instance, found for out-migration counties of Eastern Kentucky that over 70% of surveyed in-migrants were returning migrants, nearly three times the national average observed by DaVanzo and Morrison (1981). Consequently, return migrants are important to rural areas as a way of countering population loss.…”
Section: Study Area and Study Populationmentioning
confidence: 99%